THE INFLUENCE OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTION MEDIATED WITH BRAND AWARENESSAND CONSUMER BRAND ENGAGEMENT - Radha Chairunnisya; Heriyana; Syamsul Bahri; Chalirafi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the influence of social media marketing on purchase intention, mediatedby brand awareness and consumer brand engagement, among consumers of fashion clothing products in Lhokseumawe City. The background of this research is based on the increasing use of social media as a marketing tool in the fashion industry and the high consumer exposure to fashion content that does not necessarily translate into purchase intention. The method used in this study is a quantitative approach with data analysis techniques using SEM based on Partial Least Squares (PLS). Data were obtained through direct questionnaires distributed to 105 respondents who are social media users and interested in fashion clothing products in Lhokseumawe City. The results show that social media marketing has a positive and significant effect on brand awareness, consumer brand engagement, and purchase intention. Furthermore, brand awareness and consumer brand engagement have a positive and significant effect on purchase intention. Brand awareness and consumer brand engagement also mediate the effect of social media marketing on purchase intention. These findings indicate that social media marketing is a significant factor in increasing consumer purchase intention for fashion products, both directly and through increasing brand awareness and consumer engagement with the brand.